2012
DOI: 10.1002/sia.4997
|View full text |Cite
|
Sign up to set email alerts
|

Development of nano‐roughness under SIMS ion sputtering of germanium surfaces

Abstract: In this work results, about the formation of topography and roughness induced by secondary ion mass spectrometry ion beam sputtering of single crystal (100) germanium surfaces are reported and related with depth resolution issues and matrix species ( 74 Ge AE ; 74 Ge 16 O AE ; 74 Ge 2 AE ) behavior. In particular, the development of nano-roughness is studied for both O 2 + and Cs + bombardment at low energy (≤ 3 keV), using a magnetic sector instrument. Analysis was carried out in the sputtering chamber either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Topography formation is suggested also by the large variation (∼20%) of the 133 Cs 74 Ge + signal observed after SiN x /Ge interface in measurements obtained without rotation. This possible roughening processes of the Ge-layer would strongly affect the Ge sputtering yield [5,21,22]. In fact, one has to introduce a third layer correspondent to the "swollen 133 Cs 74 Ge + " region with a SR ∼20% higher than SR Ge (denoted SR Rough Ge in Fig.…”
Section: Sims Depth Scale Calibration and Crater Topographymentioning
confidence: 99%
See 1 more Smart Citation
“…Topography formation is suggested also by the large variation (∼20%) of the 133 Cs 74 Ge + signal observed after SiN x /Ge interface in measurements obtained without rotation. This possible roughening processes of the Ge-layer would strongly affect the Ge sputtering yield [5,21,22]. In fact, one has to introduce a third layer correspondent to the "swollen 133 Cs 74 Ge + " region with a SR ∼20% higher than SR Ge (denoted SR Rough Ge in Fig.…”
Section: Sims Depth Scale Calibration and Crater Topographymentioning
confidence: 99%
“…In this work, several SIMS approaches were investigated in order to define a depth profiling protocol able to ensure depth and concentration accuracies for Sn concentrations in Ge of technological relevance. It was observed that the analytical conditions less affected by interface and transient effects (Cs + sputtering at 1 keV impact energy, 64 • incidence vs. normal, collecting SnCs + positive secondary ions) induced an early and specific formation of surface topography [5][6][7][8][9] resulting in a variation of sputtering yield. In this work, a sequential formation of dots and ripples on the crater bottom was observed.…”
Section: Introductionmentioning
confidence: 99%